Whole versus Shared Ownership of Foreign Affiliates - Horst Raff; Michael Ryan; Frank Stähler (Kiel Institute for the World Economy (IfW), 2008)
This paper studies why multinational firms often share ownership of a foreign affiliate with a local partner even in the absence of government restrictions on ownership. We show that shared ownership may arise, if (i) the partner owns assets that are potentially important for the investment project, and (ii) the value of these assets is private information. In this context shared ownership acts as a screening device. Our model predicts that the multinational's ownership share is increasing in its productivity, with the most productive multinationals choosing not to rely on a foreign partner at all. This prediction is shown to be consistent with data on the ownership choices of Japanese multinationals.
Keywords: L20; F23; 330; Foreign direct investment; multinational enterprise; joint venture; productivity; Multinationales Unternehmen; Direktinvestition; Joint Venture; Asymmetrische Information; Produktivität; Eigentümerstruktur; Schätzung; Theorie; Japan